Application of Systematic Design Methods to Cultural Heritage Preservation. Issue 1 (November 2020) - Fiorineschi, Lorenzo; Barsanti, Roberta; Cascini, Gaetano; Rotini, Federico
Abstract: The preservation of cultural heritage often involves the design of systems with different purposes, as for example the devices for extraction of data from inaccessible locations and/or demonstrative models. For the latter, when the starting information about the model to be designed is incomplete, the task is not trivial, and different interpretations of the system can lead to different design outcomes. Moreover, other requirements concerning size, materials and interactivity, make this a real engineering design task, where actors with conflicting needs can be involved. Accordingly, to ensure a comprehensive fulfilment of the task, it is possible to follow engineering systematic design approaches that, even if originally developed for the development of industrial systems, can be conveniently used for different fields of application. More specifically, these design methods ensure the design of cost-effective solutions by reducing the useless and costly design iterations that often characterize non-structured procedures. In particular, the present paper shows the application of systematic methods for the interpretation, the design and the development of realistic physical models from some of the Leonardo da Vinci's machines, for the Museo Leonardiano of Vinci (Italy). The followed approach allowed to efficiently gather the starting list of design requirements, and to engage a successful interaction among the designers, the historians, the museum staff and the architect involved in the showroom design. The key points of the systematic design methodology are presented in this paper, together with some applicative examples from the Da Vinci's models. Other possible application of systematic design approaches are also presented, with the aim of showing some representative examples were the Engineering design and problem-solving methods can support the preservation of cultural heritage.